A qualitative inquiry of women managers’ competence acquisition - Idris, Norhalimah (2012)
The aim of this research is to gain further understanding of women managers’ workplace learning experiences in the context of competence acquisition. Through qualitative research design, selected numbers of women managers from three sectors such as public service, private corporations and government-linked corporations (GLCs) would be chosen for in-depth interviews followed by solicited research diaries writings. The purpose of this paper is to provide an overview of the literature on competence, gender in management, workplace learning and the use of solicited diary as a research method to provide access into the women's experiences which tend to be embedded within the complex social and cultural realities. The paper also attempts to propose a theoretical framework for the study.